Let Benny's salary = $ K
But kenny earns 142% of Benny's Salary
So, Kenny's salary = 142%of K
Kenny's salary =K
![* (142)/(100)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/rintakcmtm0o8yd3rajdom18b7xq60vdrr.png)
Kenny's salary = 1.42K
Kenny's income exceeds Benny's by =1.42K - K =$0.42 K
% by which Kenny's salary exceeds by Benny's =
![(0.42 \text K)/(\text K) * 100](https://img.qammunity.org/2019/formulas/mathematics/middle-school/tg1p7zprfx7f94c6e8kv4b9cthqn66kr4p.png)
% by which Kenny's salary exceeds by Benny's = 42%